Study of error modeling in kinematic calibration of parallel manipulators. (21st October 2016) - Wang, Liping; Liu, Yuzhe; Wu, Jun; Wang, Jinsong; Zhang, Binbin
Error modeling is the foundation of a kinematic calibration which is a main approach to assure the accuracy of parallel manipulators. This article investigates the influence of error model on the kinematic calibration of parallel manipulators. Based on the coupling analysis between error parameters, an identifiability index for evaluating the error model is proposed. Taking a 3PRS parallel manipulator as an example, three error models with different values of identifiability index are given. With the same parameter identification, measurement, and compensation method, the computer simulations and prototype experiments of the kinematic calibration with each error model are performed. The simulation and experiment results show that the kinematic calibration using the error model with a bigger value of identifiability index can lead to a better accuracy of the manipulator. Then, an approach of error modeling is proposed to obtain a bigger value of identifiability index. The study of this article is useful for error modeling in kinematic calibration of other parallel manipulators.